Analisis Ketaatan Industri Kosmetik di Kabupaten Sidoarjo Terhadap Regulasi Pengelolaan Lingkungan Hidup - Adianti, Nadia; Fadhil, Faisal (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The rapid growth of industry in Sidoarjo Regency, especially the cosmetics industry, brings new challenges in environmental management, especially related to liquid waste that has the potential to pollute water bodies. This study aims to evaluate the level of compliance of the cosmetics industry with reporting water pollution control through SIKOLING for 2023–2024. The assessment was carried out based on six main parameters, namely ownership of environmental documents, reporting of WWTP’s laboratory test results, and monitoring of water and environmental quality. The results of the study showed increase in the level of compliance between those 2 years. After the analysis was carried out, it was found that the level of industry compliance was influenced by many factors, both internal and external factors such as the company’s management and supervision from the DLHK. The local government through the DLHK has a strategic role in supervision and guidance through the SKPL Program. This study is expected to encourage increased effectiveness of supervision and industry awareness in sustainable liquid waste management. Recommendations that can be given are in the form of improvements from the government and business actors in order to build a culture of compliance and sustainable environmental awareness, so that water pollution can be prevented and the quality of the environment in Sidoarjo Regency is maintained.